Caregiver burden, perceived stress, and social support among parents of chronically Ill children in Saudi Arabia - Hebah Almulla; Ohoud Aljaloud; Halah Almulla; Seema Nasser (BMC, 2024)
Abstract Background Children with chronic illnesses pose a significant burden on parents who are directly involved in caregiving. Despite the high prevalence of chronic illnesses among children in Saudi Arabia, no study has examined caregiver burden and other related factors in the Saudi Population. Thus, this study determined the levels of caregiver burden, perceived social support, and perceived stress and their association among parents who provide care to their child with a chronic illness. Methods A cross-sectional design was used for this study. Data were collected through an online survey using standardized scales from parents who had at least one child suffering from a chronic illness or disability for more than 12 months and requiring continuous medical treatment. Results A total of 206 parents reported mild-to-moderate levels of caregiver burden, moderate levels of perceived stress, and high levels of perceived social support. Furthermore, perceived social support was significantly correlated with caregiver burden (rho = − 0.36, p < 0.01) and perceived stress (rho = − 0.45, p < 0.01), and caregiver burden was significantly associated with perceived stress (rho = 0.65, p < 0.01). Conclusions Study findings suggest that social support could play a pivotal role in designing intervention programs to mitigate the stress caused by the caregiver burden. This insight underscores the urgent need for policymakers to develop psychosocial interventions and targeted programs for caregivers of children with chronic illnesses.